The dioxygen complexes of VO2 - Hübner, Olaf; Himmel, Hans-Jörg (Zeitschrift für anorganische und allgemeine Chemie, 2021)
By matrix isolation in solid Ne and Kr, VO, VO2, and the complexes VO2(O2) with one superoxo ligand and VO2(O2)2 with one superoxo and one neutral dioxygen ligand, as well as V2O2 and V2O4 have been generated. For VO2(O2), transitions of five vibrational modes have been observed, and for VO2(O2)2, transitions belonging to seven vibrational modes, confirming and extending former Ar matrix results. Attempts to stabilise the cyclic V(O2) peroxide by use of the heavier Kr matrix were not successful. By accompanying MRCI calculations on VO2 and V(O2), vibrational frequencies have been determined. Furthermore, the investigation is assisted by density functional calculations with the TPSS functional. Possibly, also one vibrational transition of the VO3 molecule has been observed.
Im Titel ist "2" bei "VO" tiefgestellt
Gesehen am 29.03.2023